Assessment of the Suitability of the Delphi Method for Assessing the Needs of Pharmacoeconomic Studies in the Decision-Making Process - Becirovic, Sabina; Marinkovic, Valentina; Lakic, Dragana (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Increasing need for control in healthcare spendings and for publicly available services, opens new areas and topics that needs to be discussed. The aim of this paper is assessment of the technic adequacy for evaluation of knowledge level in the subject territory. Materials and Methods: Systematic review has been performed with electronic database PubMed and MEDLINE. The SPIDER model (Sample, Phenomenon of Interest, Design, Evaluation, Research Type) was used to create the search strategy, which is more suitable for qualitative research. Results: After the initial check by title and the introductory part of the abstract, 1,282 published articles were eliminated due to inadequate study design. 249 articles that were checked by abstract with a focus on methodology and sample went for additional checking. During this step, 50 articles were selected for checking the complete research, i.e., the published content. Given results has enabled us insight in Delphi method with assessment of advantages and disadvantages.
Keywords: Delphi method; Qualitative methods; Pharmacoeconomic; Decision-making